Sistem Informasi Inventory Pada Bengkel Pemeliharaan Tabung PT. Arsade Inti - Laili Ramadahyanti; Dilla Dwi Rahmatin Rusfa (LP2M Politeknik Jambi, 2020)
Inventory information system is a system for inventory of goods in warehouse. At Bengkel Pemeliharaan Tabung PT Arsade Inti Alasindo warehouse in managing goods using a computerized but simple inventory system that is using Ms. software Excel, so that in the process of managing goods that have problems in the recording process, they cannot find out the inventory data quickly and data duplication occurs, therefore an inventory information system is needed to support the inventory management process. The data method is done by interview, observation, documentation. The development of this inventory information system uses the waterfall model and the FIFO (First In First Out) method. Based on the results of the research, the authors developed an inventory information system that can be accessed by users to facilitate data processing and minimize the use of time and output in the form of reports. In the inventory information system the authors use data flow diagrams, DFD, ERD, and MySQL for data processing